Programa minha casa minha vida: uma análise do endividamento e de fatores comportamentais - Fraga, Luana dos Santos (2017)
This study aimed to identify how the beneficiaries of the “Minha Casa Minha Vida” Program (PMCMV), belonging to the Central-western Mesoregion of Rio Grande do Sul, manage their financial resources, including the payment of PMCMV funding, and how PMCMV, Attitude to Indebtedness, Financial Literacy, Financial Well-Being and Financial Management influence their Satisfaction with Life. For this, were applied 561 questionnaires, analyzed using descriptive statistics, confirmatory factor analysis, mean difference tests and regression analysis. The main results reveal that most of them have good financial habits, however, they have difficulty in saving money, have debts and have already had the name linked to the negative register. Majority of beneficiaries consider reasonable the value of the home financing payment. Among the beneficiaries of Range 1, most have already had or have arrears of the household, unlike those in Range 2 and Range 3. The main reason for default is that the installment money has been used for unexpected expenses (illness, unemployment). Individuals were satisfied with PMCMV, believing that life in general, the relationship with the neighborhood and financial life improved. Time spent with locomotion, the access to public health institutions and collective transportation, social work accomplishment and problems related to violence in the neighborhood are aspects that prevent greater satisfaction. Many have medium-to-high Financial Knowledge, develop good Financial Attitudes in relation to the concern with the financial future and savings, and good behavior regarding control and planning of expenses. They feel an intermediate level of Financial Well-Being and have a positive perception of Satisfaction with Life. The validity of all proposed behavioral constructs was confirmed; however, the scales of Satisfaction with PMCMV, Attitude to Indebtedness and Financial Attitude were quite reduced. It was found that individuals with monthly incomes between R$ 3.275,01 and R$ 5.000,00 have a higher Attitude to Indebtedness. The beneficiaries belonging to Ranges 2 and 3, men, married, with higher levels of schooling, civil servants and with income above R $ 5,000.00 have higher Financial Literacy and Financial Well-being. In relation to Satisfaction with Life, the beneficiaries of Ranges 2 and 3, men, who do not have dependents, over 48, widowed, retired, regular self-employed and public employees, with income above R$ 5.000,00 are the most satisfied. It was identified that the variables: Financial Well-Being, Financial Attitude and possessing a credit carnet exert a positive influence on Satisfaction with Life. However, the Financial Knowledge, having debts and being defaulted in PMCMV have a negative impact. Emphasis is placed on the need for greater investments in transportation and health around housing, and to offer to the beneficiaries an opportunity to learn about the importance of financial control, timely payment and savings, as well as a greater awareness that, once the beneficiaries gained the opportunity to own a house, with low installments, they need to pay the installments on time. More research is proposed on the individuals with potential to be beneficiaries and that have effective payment conditions.